2019
DOI: 10.1136/tobaccocontrol-2018-054703
|View full text |Cite
|
Sign up to set email alerts
|

Impact of flavoured tobacco restriction policies on flavoured product availability in Massachusetts

Abstract: ObjectiveThis study aimed to evaluate the effectiveness of flavoured tobacco product restriction policies in reducing availability of flavoured products in Massachusetts communities.MethodsData were obtained from surveys of tobacco retailers conducted from July 2015 to March 2017. On a community level, flavoured product availability was defined as the per cent of retailers during a given 3-month quarter that sold flavoured cigars/cigarillos, electronic cigarettes and/or e-liquids. Communities that implemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 19 publications
2
30
0
Order By: Relevance
“…Of the nine excluded studies, one study found that adolescents had a 37% lower odds of ever trying flavored tobacco products and a 28% lower odds of ever using tobacco products post ban [54], two studies found that sales of other tobacco products fell [55,56], and six considered compliance [57][58][59][60][61][62]. The studies of compliance indicated mixed levels of compliance, with flavor products still available in up to 50% of retailers that were not allowed to sell flavored tobacco and smaller stores often continuing to carry banned products with staff oblivious to the ban [58,[60][61][62]. However, compliance was found to increase over time following the ban [60] and was higher in areas where investments are made in the education of store owners and staff and when there was increased enforcement [59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the nine excluded studies, one study found that adolescents had a 37% lower odds of ever trying flavored tobacco products and a 28% lower odds of ever using tobacco products post ban [54], two studies found that sales of other tobacco products fell [55,56], and six considered compliance [57][58][59][60][61][62]. The studies of compliance indicated mixed levels of compliance, with flavor products still available in up to 50% of retailers that were not allowed to sell flavored tobacco and smaller stores often continuing to carry banned products with staff oblivious to the ban [58,[60][61][62]. However, compliance was found to increase over time following the ban [60] and was higher in areas where investments are made in the education of store owners and staff and when there was increased enforcement [59].…”
Section: Discussionmentioning
confidence: 99%
“…The studies of compliance indicated mixed levels of compliance, with flavor products still available in up to 50% of retailers that were not allowed to sell flavored tobacco and smaller stores often continuing to carry banned products with staff oblivious to the ban [ 58 , 60 – 62 ]. However, compliance was found to increase over time following the ban [ 60 ] and was higher in areas where investments are made in the education of store owners and staff and when there was increased enforcement [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 In Massachusetts jurisdictions that implemented partial flavour bans excluding menthol and adultonly establishments (bars, vape shops and tobacconists) between July 2015 and March 2017, the availability of banned products fell by 27% to 86%, depending on the city. [4][5][6] In New York City, which exempted menthol, after initial opposition (including an unsuccessful lawsuit), 7 sales of banned flavoured tobacco products declined by 87% following enforcement in November 2010, and averaging 95% compliance between November 2010 and February 2015. 7 8 (The New York law excluded e-cigarettes, which were not defined as tobacco products under New York City law and exempted eight existing tobacco bars (bars that generated at least 10% of their income from on-site tobacco sales and the rental of on-site humidors).)…”
Section: Introductionmentioning
confidence: 99%
“…Although we cannot attribute these findings solely to Providence’s POS policy, the city’s restriction on the sale of flavored tobacco products might have contributed to this decline. Evaluations of POS tobacco policies that restricted the sale of flavored tobacco products have been conducted in New York City (13,14), Minneapolis and Saint Paul, Minnesota (15), and Massachusetts (16). These policies take different approaches, but the evaluations show that the availability and sale of these products declined significantly after policy enforcement.…”
Section: Implications For Public Healthmentioning
confidence: 99%